2020
DOI: 10.1101/2020.05.04.20090944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute Kidney Injury in Hospitalized Patients with COVID-19

Abstract: Importance: Preliminary reports indicate that acute kidney injury (AKI) is common in coronavirus disease (COVID)-19 patients and is associated with worse outcomes. AKI in hospitalized COVID-19 patients in the United States is not well-described. Objective: To provide information about frequency, outcomes and recovery associated with AKI and dialysis in hospitalized COVID-19 patients. Design: Observational, retrospective study. Setting: Admitted to hospital between February 27 and April 15, 2020. Participant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
2
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 19 publications
2
42
2
8
Order By: Relevance
“…In our study we found that the median of age of patients with AKI secondary to COVID-19 was similar to other published studies such as Hirsch, et al and Chan, et al [9,10]. However, a meta-analysis published recently composed primarily of Chinese patients showed a great variability in the age, including patients from 47 to 70 years old [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study we found that the median of age of patients with AKI secondary to COVID-19 was similar to other published studies such as Hirsch, et al and Chan, et al [9,10]. However, a meta-analysis published recently composed primarily of Chinese patients showed a great variability in the age, including patients from 47 to 70 years old [11].…”
Section: Discussionsupporting
confidence: 91%
“…The median of creatinine on admission in our study differs from the one reported in other studies [9,10]. This is due to the fact that the serum creatinine obtained in our study was previous to the start of RRT; additionally, our data came from medical charts, not having the baseline serum creatinine previous to hospitalization.…”
Section: Discussioncontrasting
confidence: 79%
“…However, we found a pooled AKI prevalence of 32% and a New York report cited 46% of hospitalized and 68% of ICU COVID-19 cases with AKI with 34% of those in ICU requiring replacement renal therapy (RRT), and with an OR of 20.9 (95% CI 11.7 to 37.3) for AKI vs non-AKI associated ICU mortality [58]. Along with our analysis, this raises the concern that AKI maybe seriously under appreciated in critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 68%
“…of ICU COVID-19 cases with AKI with 34% of those in ICU requiring replacement renal therapy (RRT), and with an OR of 20.9 (95% CI 11.7-37.3) for AKI vs non-AKI associated ICU mortality [58].…”
Section: Discussionmentioning
confidence: 99%